Specialty imaging : dental implants - Tamimi, Dania Faisal (Salt Lake City, Utah : Amirsys Publishing, Inc., 2014)
'Specialty Imaging: Dental Implants is a unique textbook written by a team of experts representing every specialty that deals with implant dentistry, but led by an oral and maxillofacial radiologist. This collaborative effort has produced a truly comprehensive reference for anyone involved with imaging for dental implant purposes, including oral and maxillofacial radiologists, oral surgeons, periodontists, technicians, and general dentists. Specialty Imaging: Dental Implants is organized in such a way that it guides the reader from the basics to the post-procedure management of implants. The main topics include: anatomy and nomenclature of dental implants as well as biological and biomechanical considerations; imaging toolbox options, with the utilization of these options for planned implant site evaluation; discussion of common pathology that may be encountered in the analysis of radiographic data with applicable implant correlations; available alveolar process augmentation options based on radiographic imaging data; imaging protocols for post-surgical implant procedure and the radiographic appearances of success; and lastly, the radiographic appearance of complications associated with dental implant treatment. Lead by a board-certified oral and maxillofacial radiologist, Dania Tamimi, BDS, DMSc, and meticulously constructed by her and her multi-specialized team of authors, this reference encourages more inclusion of and collaboration with oral and maxillofacial radiologists for implant planning cases, and educates clinicians on how to use imaging tools efficiently and effectively to get the most out of their radiographic imaging data, resulting in an overall better treatment outcomes for the patient. As with all Amirsys references, all of the information is distilled into succinct, bulleted text with thousands of images and illustrations. Coupled with a companion eBook, this volume will surely become the standard reference textbook for all involved in implant dentistry.'--Provided by publisher.
This book includes online access at http://ebooks.amirsys.com, please refer library staff for the password.
Includes bibliographical references and index.
Keywords: Dental Implantation -- methods -- Atlases; Radiography, Dental -- methods -- Atlases